Reframe of Fowler-Northeim Approach for Electron Field Emission of a Vertical Silicon Nanowires - Singh, D (Springer Science and Business Media B.V., 2023)
Determining the electron field emission (FE) turn-on field of the silicon nanowires(SiNWs) array can better adapt to the application of field-assisted photocathode. Here, we report the observations of FE from SiNWs grown on n-type Si(100) by utilizing silver induce chemical etching (SICE) approach. The growth of SiNWs is confirmed by XPS and XRD spectra and the optical band gaps, studied from the Kubelka-Munk function reveals the red shifting behavior. The grown SiNWs show an excellent FE property. The new proposed analytical framework enables one to understand the FE properties in better sense as compared to the conventional utilized framework, named as Fowler-Nordhiem (F-N) approach. It improves the analysis by introducing a new parameter i.e. boost-factor to take care of the FE data in totality unlike the traditional framework, where only currents were considered for higher electric fields. Moreover, it also addresses the ambiguity present in the previously used approach. A quantum mechanical model is adopted to explain the improved FE properties from these NWs by using the concept of tunneling probability. These results can enrich our knowledge on the FE of SiNWs and are highly related to the development of the next-generation of Si nano-electronic devices. © 2023, The Author(s), under exclusive licence to Springer Nature B.V.